Intensive Care Usage by HIV-Positive Patients in the HAART Era. (30th October 2011) - Turtle, L.; Vyakernam, R.; Menon-Johansson, A.; Nelson, M. R.; Soni, N.
Abstract : In the 1980s the outlook for patients with the acquired immunodeficiency syndrome (AIDS) and critical illness was poor. Since then several studies of outcome of HIV+ patients on ICU have shown improving prognosis, with anti-retroviral therapy playing a large part. We retrospectively examined intensive care (ICU) admissions in a large HIV unit in London. Between April 2001 and April 2006 43 patients were admitted to the ICU. The mean age of patients was 44 years and 74% were male. Fifty-six percent of admissions were receiving anti-retroviral therapy and 44% had an AIDS defining diagnosis. The median CD4 count was 128 cells/mL and the median APACHE II score was 21. The commonest diagnostic ICU admission category was respiratory disease. This group experienced higher mortality despite slightly lower APACHE II scores, though this did not achieve statistical significance. The follow up period was one year or until April 2007, when data were censored. ICU mortality was 33%, in hospital mortality was 51% and overall mortality at the end of the study period was 67%. Median survival was 1008 days. The CD4 count did not predict long-term survival, although the sample size was too small for this to be conclusive.